2015
DOI: 10.1002/ptr.5435
|View full text |Cite
|
Sign up to set email alerts
|

Zingerone activates VMAT2 during MPP+‐induced Cell Death

Abstract: Parkinson's disease (PD) is characterized by a progressive and selective loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and striatum. 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is used to produce an animal model for PD, and it is converted to 1-methyl-4-phenylpyridine (MPP(+)) in animals. MPP(+) accumulation leads to neuronal cell death. Vesicular monoamine transporter 2 (VMAT2) regulates the accumulation of monoamine neurotransmitters into synaptic vesicles and is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…VMAT2, localized on vesicular membranes in dopaminergic neurons, is a strong candidate that functions to transport cytosolic DA and exogenous neuronal toxins into synaptic vesicles and is involved in neuroprotection against neurotoxin-induced cell death [39,40]. The de cits of VMAT2 have been implicated in the dopaminergic neurons loss which is considered as a typical pathological feature of PD [41].…”
Section: Discussionmentioning
confidence: 99%
“…VMAT2, localized on vesicular membranes in dopaminergic neurons, is a strong candidate that functions to transport cytosolic DA and exogenous neuronal toxins into synaptic vesicles and is involved in neuroprotection against neurotoxin-induced cell death [39,40]. The de cits of VMAT2 have been implicated in the dopaminergic neurons loss which is considered as a typical pathological feature of PD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine distribution and signaling are mainly regulated by dopamine transporter (DAT), which transports dopamine into the presynaptic region, and vesicular monoamine transporter 2 (VMAT2), which transports dopamine from the cytosol into synaptic vesicles, facilitating its release in the synaptic cleft. 45 VMAT2 also acts neuroprotectively in neurotoxin-induced neuronal cell death, 46 and post-mortem studies have demonstrated that the function of VMAT2 is reduced in PD patients. 47 It has been demonstrated that zingerone administration was associated with increased neuronal cell viability in MPTPinjected animal models of PD and MPP + -treated dopaminergic neuronal cells in vitro, without affecting inflammatory responses or oxidative stress but by promoting extracellular signal-regulated kinase (ERK) activation and VMAT2 expression.…”
Section: Regulation Of Synaptic Transmission In Pdmentioning
confidence: 99%
“…47 It has been demonstrated that zingerone administration was associated with increased neuronal cell viability in MPTPinjected animal models of PD and MPP + -treated dopaminergic neuronal cells in vitro, without affecting inflammatory responses or oxidative stress but by promoting extracellular signal-regulated kinase (ERK) activation and VMAT2 expression. 46 ERK is implicated in several signaling pathways, including the upregulation of the transcription factor cAMP response element-binding protein (CREB). The promoter of VMAT2 gene can bind to CREB, and ERK inhibition was associated with reduced activity of VMAT2 promoter.…”
Section: Regulation Of Synaptic Transmission In Pdmentioning
confidence: 99%
See 2 more Smart Citations